Moderating Effect of Organizational Capability on the Relationship Between Business Intelligence Capability and Performance Among Public Listed Firms in Kenya - Edward Buhasho; Agnes Wausi; James Njihia (European Scientific Journal, ESJ, 2021)
Business Intelligence remains a primary focus in many organisations and it naturally attracts significant investment. Existing literature is nebulous and fragmented on the real impact and how well the insights induced by this technology have been transformed into successful business learning. Consequently, this paper focuses on determining the influence of organizational capabilities on the relationship between Business Intelligence capability and firm performance. The study employed interdisciplinary theories to realize the research objective, namely Information Systems Capability theory and Organizational Learning theory. In addition, the study was conducted using mixed methods research methodology and a crosssectional approach. The study used structural equations modeling technique (Partial Least Squares approach- SEM-PLS) to analyse quantitative data and validate the developed research model. Thematic analysis aided by Atlas.ti version 8 software was applied to analyse qualitative data. Findings of quantitative and qualitative strands of the study were triangulated at the data analysis stage based on convergence model. Results revealed that organizational capability has a positive and significant moderating impact. The findings provide fresh enlightenment into current Business Intelligence literature and opportunities for future research with implications for management, policy makers, and academia.